IMPLEMENTATION OF CASH WAQF IN INDONESIAN SYARIAH BANK IN THE PERSPECTIVE OF LAW 41/2004 AND SHARIA BUSINESS LAW - Mohamad Idham; Sawitri Yuli Hartati S; Sadath M. Nur (RADJA PUBLIKA, 2026)
Cash waqf is an Islamic philanthropic instrument with strategic potential in strengthening an inclusive and sustainable economy, particularly in the post-pandemic period. In Indonesia, cash waqf has gained legal legitimacy through Law Number 41 of 2004 concerning Waqf and the support of a fatwa from the National Sharia Council of the Indonesian Ulema Council. However, there is a gap between the potential of cash waqf and its implementation in Islamic financial institutions. This study aims to analyze the implementation of cash waqf at Bank Syariah Indonesia and assess its contribution to the development of Islamic business law in Indonesia. This study uses an empirical juridical method with a qualitative approach, through an analysis of laws and regulations, fatwas, policy documents, and cash waqf management practices. The results show that normatively, the implementation of cash waqf is in accordance with positive law and Sharia principles. However, substantively, its management is not optimal in supporting real sector financing and empowering the community's economy. The main obstacles include low literacy in cash waqf, limited professionalism of nazhir (managers), and suboptimal technical regulations. This research emphasizes the need for strengthening regulations, increasing institutional capacity, and synergy between authorities so that cash waqf functions optimally as a legal instrument for socially just sharia business.